Children’s Language Acquisition due to the Influence of Animation Film - Tri Indah Rezeki (English Teaching and Linguistics Journal (ETLiJ), 2021)
Children’s language acquisition is affected by several factors. One of the factors is environment. Film is one of environment factors that influences children’s language acquisition at the linguistic period. This can be seen from the use of words, expressions or sentences that the children imitate in their daily conversations. This study aims to analyze the phenomenon of children’s language acquisition due to the influence of animation film. Spesifically, this study discussed how many childrens’ vocabulary acquired after watching animation film. In this case, the researcher took an animation film namely Omar Hana film.  This study was a qualitative research with descriptive research design. The data was collected from childrens’ utterances aged 3 years old and 5 years old in daily conversation. In collecting the data, the researcher used observation, diary, and interview. The results of the study indicated that Omar Hana film has an impact on childrens’ language acquisition aged 3 years old and 5 years old in their daily conversations. It was found that there were 10 words often used by the children to imitate Omar Hana’s utterances in daily conversation. In other words, the words that Omar Hana used in the film influenced the children’s language acquition aged 3 years old and 5 years old.